Hakikat Pendidikan Islami - Gunawan Adnan (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2017)
Islamic education is a concept of education based on universal true values and the truthfrom Allah SWT Who has prepared the clear principle of education that enlightens,prospers, and saves mankind in this world and here after. One of the main goals of Islamiceducation is to make people aware and persistent (istiqama) with the basic principleof men creation to serve for Allah (hablummninallah) and become rahmatanlil’alamin,useful and beneficent for the whole universe, either for the men or for the nature(hablumminanaas wahablumminal ‘aalamien) as the consequence of serving the missionof being khalifatullah in the world. Hence, the concept of Islamic education needs to meetseveral main requirements. First, it needs to have a clear goal, objective, and target.Second, the real and absolute educator is Allah SWT, the creator of fitra, the talent giver,the maker of all nature of law related to development, advancement, and interactionas well as He is the One presupposing the rules to actualize completeness, benefit andhappiness of the fitra. Third, education demands for the realization of gradual programby developing teaching and learning activities in line with children development. Fourth,the role of educator must be in accordance with purpose of his creation by Allah. Thelogical consequence of this issue is that Islamic education requires an Islamic curriculum,approach and methodology based on the essence values of the Qur’an and hadith. Thispaper shall discuss concisely all important points related to the concept of Islamiceducation covering the definition and the superiorities of Islamic education.